Evaluation of Levamisole pharmacokinetic and milk excretion in dairy goats - Lúpori, Jorgelina Lucrecia (2021)
Levamisole (LVM) is a nematodicidal compound available for veterinary medical use for over 50 years. Since the widespread development of drug resistance is a serious productive inconvenient, LVM is currently used extralabel as a therapeutic alternative in dairy sheep and goats. Thus, information on drug residual concentrations in milk is needed to assure protect consumer`s safety. The current work aimed to evaluate the concentration profiles of LVM in plasma and its pattern of milk excretion in lactating dairy goats treated at different stages of lactation.